An Afrotropic element at the north-western periphery of the Oriental Region: Pseudomicrommata mokranica sp. nov. (Araneae: Sparassidae) - Majid Moradmand; Alireza Zamani; Peter Jäger (Muséum d'histoire naturelle, 2022)
The surprising discovery of a new species of grass huntsman spider, Pseudomicrommata mokranica sp. nov. (male female), belonging to "the African clade", is reported and described from south-eastern Iran, more than 4000 km away from the nearest recorded locality of the genus in Kenya. Similar vicariant occurrences of other sparassid taxa in Africa and Asia are discussed.